Pelatihan Penyusunan Laporan Arus Kas pada Nagata Motor - Nazli Fahada; Jhon Lismart Benget. P.; Thomas Firdaus Hutahaean (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2023)
The purpose of this community service is to provide training in the preparation of cash flow reports, reports can describe cash in and cash out. This training in preparing cash flow reports in Community Service uses a participatory training approach. This training includes: (1) Counseling on the preparation of cash flow statements. Implementation of training activities to prepare cash flow reports, (2) Training activities to prepare cash flow reports are carried out after counseling activities on preparing cash flow reports. (3) Monitoring and Evaluation in Community Service activities aims to identify the extent of success in preparing cash flows. From the results of community service that training in preparing cash flow reports at Nagata Motor has succeeded in increasing knowledge of preparing cash flow reports.